The Association Between Hyperlipidemia and In-Hospital Outcomes in Takotsubo Cardiomyopathy - Li P (Dove Medical Press, 2021)
Pengyang Li,1,* Xiaojia Lu,2,* Catherine Teng,3 Michelle Hadley,4 Peng Cai,5 Qiying Dai,5 Bin Wang2,6 1Department of Medicine, Saint Vincent Hospital, Worcester, MA 01608, USA; 2Department of Cardiology, The First Affiliated Hospital of Shantou University Medical College, Shantou, Guangdong 515041, People’s Republic of China; 3Department of Medicine, Yale New Haven Health-Greenwich Hospital, Greenwich, CT 06830, USA; 4Division of Cardiology, Saint Vincent Hospital, Worcester, MA 01608, USA; 5Department of Mathematical Sciences, Worcester Polytechnic Institute, Worcester, MA 01609, USA; 6Clinical Research Center, The First Affiliated Hospital of Shantou University Medical College, Shantou, Guangdong 515041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bin WangDepartment of Cardiology, The First Affiliated Hospital of Shantou University Medical College, 57 Changping Road, Shantou, Guangdong 515041, People’s Republic of ChinaTel +86-75488905399Fax +86 75488259850Email wangbin_pku@126.comPurpose: Hyperlipidemia (HLD) is one of the most common cardiovascular risk factors and is prevalent in patients with takotsubo cardiomyopathy (TCM), but the association between HLD and TCM patients’ outcomes is unclear. We investigated the impact of HLD on the in-hospital outcomes of TCM patients.Patients and Methods: Our retrospective cohort study used the latest available data from the National Inpatient Sample (2016– 2017). Using the ICD-10 code, we identified 3139 patients with a primary diagnosis of TCM, 1530 of whom had HLD. We compared in-hospital outcomes between HLD and non-HLD groups before and after propensity score matching.Results: In the unmatched cohort, the HLD group had lower incidences of cardiac arrest, cardiogenic shock, and acute respiratory failure (ARF); shorter length of stay (LOS); and lower total charges (All p< 0.05). In-hospital mortality (p=0.102) and ventricular arrhythmia (p=0.235) rates did not differ. After propensity score matching, the HLD group had lower rates of in-hospital mortality (1.1% vs 2.4%, p=0.027), ARF (9.1% vs 12.1%, p = 0.022) and cardiogenic shock (3.4% vs 5.6%, p=0.012), shorter LOS (3.20 ± 3.27 days vs 3.57 ± 3.14 days, p=0.005), and lower total charges (p=0.013). The matched groups did not differ significantly regarding cardiac arrest (p=0.141), ventricular arrhythmia (p=0.662) or acute kidney injury (AKI) (p = 0.167).Conclusion: Counterintuitively, HLD was associated with better in-hospital outcomes in both the unmatched and propensity-matched cohorts of hospitalized TCM patients. Further studies are needed to investigate the mechanisms that may contribute to the association in TCM patients with HLD.Keywords: takotsubo cardiomyopathy, hyperlipidemia, mortality